The Ecumenical Dimension of Ecclesial Reforms in Francisco’s Teaching: Provisional Balance Sheet and Perspectives - Wolff, Elias (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
The magisterium of Pope Francis reinvigorates the process of reception of Vatican II through initiatives of reforms in the Church, the resizing of the theological mentality, the affirmation of synodality, a new way of exercising the Petrine ministry, among others. This happens in the effort of an «outgoing» Church in a missionary perspective and in the dialogue with cultures, Churches and religions. The purpose of this article is to verify the ecumenical implications of these proposals. The method is the qualitative analysis of documents and pronouncements in which the pope expresses, explicitly or implicitly, the conciliar ecumenical conviction. The conclusion is that ecumenism is a clear option in Francis’ magisterium and in his Church reform initiatives. Although he has not, until now, worked on doctrinal issues from an ecumenical perspective, he creates a new ecclesial situation that favors doctrinal dialogue between the different Churches.
Keywords: Pope Francis; Church; Vatican II; reform; synodality; ecumenism